Shield slag synchronous grouting material and preparation method thereof

By preparing a specific ratio of shield slag synchronous grouting materials, the problem of low utilization rate of shield slag is solved, efficient utilization is achieved, and energy waste and environmental impact are reduced.

CN119735399APending Publication Date: 2025-04-01CHINA RAILWAY 22ND BUREAU GRP RAIL ENG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411627002.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The low utilization rate of existing shield slag has led to energy waste and environmental impact.

Method used

By preparing a shield slag synchronous grouting material, the material consists of cement, fine aggregate, fly ash, bentonite and curing agent, a specific ratio and preparation method is used to form a grouting material with fixed and stable strength.

Benefits of technology

It improves the utilization rate of shield slag, avoids energy waste, and is more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735399A_ABST
    Figure CN119735399A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of shield slag recycling, and specifically to a shield slag synchronous grouting material, the grouting material is prepared from the following materials: 300-500 parts of cement, 100-200 parts of fine aggregate, 150-300 parts of fly ash, 500-1500 parts of bentonite, and 180-320 parts of curing agent; a method for preparing a shield slag synchronous grouting material, the preparation method comprising: preparing 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water; using a stirrer to stir the materials at a low speed to stir them evenly; then the shield curing agent is added into the water to dilute it, and water is added to the material to the water-binder ratio required by the formula; the stirrer stirs at a high speed until it is uniform, forming a shield slag synchronous grouting liquid. The present application can generate a grouting material with good fixation and strong stability by recycling the shield slag, thereby making the utilization rate of the shield slag higher, avoiding a large amount of energy waste, and being more environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of shield slag recycling, and specifically relates to a shield slag synchronous grouting material and a preparation method thereof. Background Art

[0002] Shield slag is a mixture produced during the excavation process of the shield machine, mainly composed of soil, rock fragments and cement slurry. Its properties vary depending on the geological conditions and shield technology. It usually has high viscosity and certain strength. Traditionally, shield slag is regarded as waste and needs to be handled and removed through transportation and treatment. However, with the popularization of the concept of sustainable development, reusing shield slag as synchronous grouting material has significant environmental and economic advantages. Reusing shield slag grouting residue not only reduces dependence on original resources, but also reduces the cost of waste treatment and transportation, while reducing negative impacts on the environment.

[0003] The existing shield slag utilization rate is low, resulting in a large amount of energy waste and bringing environmental impact. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a shield slag synchronous grouting material and a preparation method thereof to solve the above technical problems.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a shield slag synchronous grouting material, characterized in that the grouting material is prepared from the following materials in parts: 300-500 parts of cement, 100-200 parts of fine aggregate, 150-300 parts of fly ash, 500-1500 parts of bentonite, and 180-320 parts of curing agent.

[0006] Preferably, the grouting material is prepared from the following materials: 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water.

[0007] Preferably, the cement is ordinary Portland cement produced by Guangxi Guigang Cement Company, which has a fixed composition and stable performance, a strength grade of 42.5Pa, and the fine aggregate is medium-fine sand screened from on-site slag.

[0008] Preferably, the fly ash is Class F Grade I fly ash, the fineness of the fly ash is 9.2%, the water requirement ratio is 89%, the loss on ignition is 4.6%, the moisture content is 0.6%, and the SO3 is 1.1.

[0009] Preferably, sodium bentonite is selected, and the chemical composition percentage of sodium bentonite is: SiO2 is 63.12%, Al2O3 is 15.23%, Fe2O 3为5.50%, Na2O is 2.36%, MgO is 3.33, K2O is 1.98, and CaO is 1.42.

[0010] Preferably, water-based epoxy resin is used as the main agent, and silicone waterproofing agent, photoinitiator and cellulose dispersant are added as external additives to form the organic component of the photoinitiated latent slag solidifier. The inorganic component is a composite of cement and various mineral components. The physical and mechanical indicators of the soil are changed through cementitious materials, and the loose and weak slag is transformed into a civil engineering material with certain engineering properties.

[0011] A method for preparing shield slag synchronous grouting material, characterized by:

[0012] S1: Prepare 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water.

[0013] Preferably, the step of S2 is:

[0014] Prepare the required materials according to the formula ratio, including cement, fine aggregate, fly ash, bentonite, and curing agent;

[0015] Set the mixer to a low speed to ensure that the materials are thoroughly mixed without excessive bubbles or separation.

[0016] Put the pre-weighed cement, filler and other solid raw materials into the mixer in sequence;

[0017] Start the agitator and continue to stir the materials at a low speed according to the designed stirring time;

[0018] During the mixing process, stop the machine regularly to check the state of the mixture and adjust the speed of the agitator according to the state of the mixture.

[0019] Preferably, the step of S3 is:

[0020] Slowly add the shield curing agent into the prepared clean water;

[0021] Use a stirrer to mix the curing agent and the aqueous solution;

[0022] Calculate the required water-binder ratio based on the predetermined design formula;

[0023] According to the calculated water-binder ratio, slowly add the pre-diluted curing agent solution to the mixed shield slag synchronous grouting material. During the process of adding water, continue stirring to ensure that the curing agent solution and the material are evenly mixed;

[0024] Mix the whole material with mixer at low speed.

[0025] Preferably, the step of S4 is:

[0026] Set the blender to high speed blending mode and start the blender;

[0027] Continue stirring for 5-30 minutes in high-speed stirring mode;

[0028] Stop the machine during the process to check the state of the mixture, check for lumps and stratification;

[0029] After completing high-speed stirring, stop the machine to check the uniformity and fluidity of the mixture;

[0030] After mixing is completed, the shield slag synchronous grouting liquid is immediately transported to the construction site.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] This application can generate grouting materials with good fixity and strong stability through the reuse of shield slag, thereby making the utilization rate of shield slag higher, avoiding a large amount of energy waste, and being more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a preparation flow chart of the present invention;

[0034] Figure 2 It is a schematic diagram of the consistency of the synchronous grouting liquid of the present invention;

[0035] Figure 3 It is a schematic diagram of the setting time of the synchronous grouting liquid of the present invention;

[0036] Figure 4 It is a schematic diagram of the compressive strength of the slag synchronous grouting material of the present invention; DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0039] The present invention provides a technical solution: a shield slag synchronous grouting material, characterized in that the grouting material is prepared from the following materials in parts: 300-500 parts of cement, 100-200 parts of fine aggregate, 150-300 parts of fly ash, 500-1500 parts of bentonite, and 180-320 parts of curing agent.

[0040] Furthermore, the grouting material is prepared from the following materials: 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water.

[0041] Furthermore, the cement is ordinary Portland cement produced by Guangxi Guigang Cement Company, which has a fixed composition and stable performance, a strength grade of 42.5Pa, and the fine aggregate is medium-fine sand screened from on-site slag.

[0042] Furthermore, the fly ash selected is Class F Grade I fly ash, the fineness of the fly ash is 9.2%, the water requirement ratio is 89%, the loss on ignition is 4.6%, the moisture content is 0.6%, and the SO3 is 1.1.

[0043] Furthermore, sodium bentonite is selected, and the chemical composition percentage of sodium bentonite is: SiO2 is 63.12%, Al2O3 is 15.23%, Fe2O 3为 5.50%, Na2O is 2.36%, MgO is 3.33, K2O is 1.98, and CaO is 1.42.

[0044] Furthermore, the organic component of the photoinitiated latent slag solidifier is formed by taking water-based epoxy resin as the main agent and adding silicone waterproofing agent, photoinitiator and cellulose dispersant as external additives. The inorganic component is compounded by cement and various mineral components, and the physical and mechanical indicators of the soil are changed through cementitious materials, so that the loose and weak slag is transformed into civil engineering materials with certain engineering properties.

[0045] A method for preparing shield slag synchronous grouting material, characterized in that the preparation method comprises:

[0046] S1: Prepare 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water;

[0047] The further steps of S2 are:

[0048] Prepare the required materials according to the formula ratio, including cement, fine aggregate, fly ash, bentonite, and curing agent;

[0049] Set the mixer to a low speed to ensure that the materials are thoroughly mixed without excessive bubbles or separation.

[0050] Put the pre-weighed cement, filler and other solid raw materials into the mixer in sequence;

[0051] Start the agitator and continue to stir the materials at a low speed according to the designed stirring time;

[0052] During the mixing process, stop the machine regularly to check the state of the mixture and adjust the speed of the agitator according to the state of the mixture.

[0053] Furthermore, the steps of S3 are:

[0054] Slowly add the shield curing agent into the prepared clean water;

[0055] Use a stirrer to mix the curing agent and the aqueous solution;

[0056] Calculate the required water-binder ratio based on the predetermined design formula;

[0057] According to the calculated water-binder ratio, slowly add the pre-diluted curing agent solution to the mixed shield slag synchronous grouting material. During the process of adding water, continue stirring to ensure that the curing agent solution and the material are evenly mixed;

[0058] Mix the whole material with mixer at low speed.

[0059] Furthermore, the steps of S4 are:

[0060] Set the blender to high speed blending mode and start the blender;

[0061] Continue stirring for 5-30 minutes in high-speed stirring mode;

[0062] Stop the machine during the process to check the state of the mixture, check for lumps and stratification;

[0063] After completing high-speed stirring, stop the machine to check the uniformity and fluidity of the mixture;

[0064] After mixing is completed, the shield slag synchronous grouting liquid is immediately transported to the construction site.

[0065] The preparation steps of shield slag synchronous grouting material are as follows: weigh the corresponding weight of cement, slag and sand, use a stirrer to stir the materials at a low speed to mix them evenly, and the material ratio is shown in Table 1. Then add the shield curing agent into the water to dilute it, and add water to the material to the water-binder ratio required by the formula. Stir the stirrer at a high speed until it is uniform to form a shield slag synchronous grouting liquid. At the same time, prepare a traditional cement mortar synchronous grouting liquid as a control group, and the material ratio is shown in Table 2.

[0066] Table 1 Soil synchronous grouting material ratio

[0067]

[0068]

[0069] Table 2 Blank group ratio

[0070]

[0071] (1) Slump test method

[0072] Slump is a basic indicator for evaluating the workability of fresh concrete containing coarse particles. It is measured using a trumpet-shaped slump barrel with a height of 300mm, a bottom diameter of 200mm and an upper diameter of 100mm. The slump detection process consists of the steps of filling the slump barrel, tamping, leveling, lifting the barrel and measuring. The fertilizer trough backfill material is filled into the slump barrel three times. After each filling, a tamping rod is used to tamp 25 times evenly along the barrel wall from the outside to the center. After tamping, scrape off the excess fertilizer trough backfill material and smooth it with a trowel. Then, lift the slump barrel vertically and steadily, and manually measure the height difference between the barrel height and the highest point of the fertilizer trough backfill material specimen after collapse with a ruler, which is the slump value of the fertilizer trough backfill mixture.

[0073] (2) Setting time

[0074] The setting time of fertilizer tank backfill material is tested by using a penetration resistance meter. The fertilizer tank backfill mixture prepared with shield slag is taken, and the slurry is screened out as quickly as possible with a square hole sieve with a nominal diameter of 5.00m, and then loaded into a test mold. The surface of the slurry is leveled so that it is about 10mm lower than the upper edge of the test mold. The slurry sample tube is placed on the penetration resistance meter, and the end of the probe touches the slurry surface. Then, within 10 seconds, the probe is slowly and evenly penetrated into the slurry to a depth of 25mm to record the penetration pressure and test time. The setting time measurement starts from the moment when cement contacts water, and then tests are performed every 0.5h. The number of measurements can be increased when it is close to the initial setting. The penetration resistance test should be carried out at least 6 times between 0.2 and 28MPa. The last unit area penetration resistance should not be less than 28MPa. Each group of samples is tested three times, and the average value is calculated.

[0075] (3) Unit sample and maintenance method

[0076] The test block should be a 150mm cube, so the present invention uses a 150mm×150mm×150mm cube test mold as the unit body molding mold.

[0077] The specific steps of forming, demoulding and curing of the unconfined compressive strength specimen are as follows:

[0078] ①Apply a layer of release agent on the inner surface of the test mold;

[0079] ② Pour the mixed fertilizer tank backfill material into the test mold, gently vibrate it, scrape off the excess part with a scraper and finish it;

[0080] ③ Place the test mold in a standard curing box with a temperature of 20±2℃ and a relative humidity of ≥95% for curing;

[0081] ④ Demould after 24 hours and then place the sample back into the standard curing room for further curing.

[0082] (4) Unconfined compressive strength test method

[0083] The test instrument uses a universal testing machine, the manufacturer is Zhejiang Lixian Testing Instrument Manufacturing Co., Ltd., the machine model is YAW-300D, and the maximum load is 300kN;

[0084] According to the curing method of the specimens in the previous section, unconfined compressive strength tests were carried out 3d, 7d, and 28d from the date when the specimens were cast in the mold. Three specimens were set at each age in each test group. Loading was carried out at a speed of 1mm / min until 2 minutes after the specimen was destroyed or the strain was greater than 10%, and the test was stopped.

[0085] (5) Scanning electron microscopy

[0086] Scanning electron microscopy is a common method for studying the microstructural characteristics and strength growth mechanism of materials. The fertilizer trough backfill material prepared with shield slag is a mixture of various materials. With the progress of hydration reaction, its microstructure will change, which will have a great impact on its working performance and mechanical properties. This paper adopts the Czech TESCAN field emission scanning electron microscope MIRALM, observes the morphology of the product through the Phenom LE field emission scanning electron microscope, and selects three points for elemental composition analysis using EDS. Before the test, take a small sample and attach it to the conductive adhesive. All samples are treated with palladium spraying and Czech TESCAN scanning electron microscope.

[0087] Performance of synchronous grouting materials based on shield slag

[0088] (1) Consistency

[0089] For synchronous grouting materials, the consistency is required to be moderate. If the slurry is too thin, it will cause serious water seepage of the grouting material, poor water retention, and the later shrinkage of the grouting body will also increase; if the grouting material is thicker, the fluidity of the slurry will become worse. Although the water retention is good and the shrinkage deformation is small, it is not conducive to pumping construction. The consistency of the synchronous grouting material for slag soil varies with different factors such as Figure 2As shown in the figure, as the water-solid ratio increases, the free water in the slurry will increase with the increase of the water-binder ratio, and the slurry consistency will increase linearly; as the soil-sand ratio increases or the cement content increases, the slurry consistency gradually decreases. As the cement content increases, more mixing water is adsorbed on the surface of cement particles, so the slurry consistency will increase if the cement content is reduced. The curing agent has no obvious effect on the slurry consistency due to its small dosage. In summary, the slurry consistency is mainly affected by the water-solid ratio, soil-sand ratio, and cement content. When the water-solid ratio reaches 0.39, the consistency of the solidified slag slurry is higher than that of the synchronous grouting material in the control group, which can meet the requirements of synchronous grouting workability.

[0090] (2) Setting time

[0091] Setting time is an important parameter in the design of synchronous grouting materials. If the setting time is too short, the slurry will lose fluidity before being injected into the gap behind the shield section, which may cause residual slurry to block the pipeline. If the setting time is too long, the slurry will be easily diluted by groundwater, resulting in low slurry strength, which is not conducive to controlling stratum deformation. Therefore, the setting time of the slurry needs to be controlled within an appropriate range. According to research data, the setting time of synchronous grouting materials should be within the range of 3.5 to 8 hours. The setting time of the slag synchronous grouting liquid and the control group cement mortar synchronous grouting liquid was tested. Figure 3 As shown in the figure, the setting time of the synchronous grouting material in the control group is 7.3h, and the setting time of the synchronous grouting material of the slag soil can be adjusted within the range of 3.4 to 9.2h. The setting time of the slurry increases with the increase of the water-solid ratio. This is mainly attributed to the increase of the water content in the slurry system and the increase of the distance between the solid particles caused by the increase of the water-solid ratio, which reduces the curing reaction rate and weakens the bonding effect between the generated gel products, thereby causing the gel products to flocculate and overlap to form a basic skeleton. The macroscopic performance is the increase of the setting time. At the same time, with the increase of cement content and slag content, the setting time is shortened. The solidified soil slurry mainly relies on the reaction between cement, slag soil and curing agent to form gel products. The increase of reactants will increase the reaction rate and shorten the setting time.

[0092] (3) Slurry stability

[0093] After the synchronous grouting materials are prepared, the slurry needs to be stored in the slurry tank for a period of time before use. During this period, solid particles may settle and free water may float under the action of gravity. The phenomenon of slurry stratification and clear water precipitation on the surface is called seepage. The seepage rate is an important indicator for determining the stability of slurry. A small seepage rate indicates that the slurry is uniform and dense inside, and the strength distribution of the formed grouting body is uniform. It is not easy to cause serious segregation and stratification during construction and transportation. At the same time, it can also avoid the blockage of the grouting pipe due to the precipitation of solid particles. The stone rate of slurry is also an important indicator of slurry stability, which can reflect the effect of slurry on controlling stratum deformation to a certain extent. The smaller the stone rate of slurry, the fewer the back-wall voids that can be filled by synchronous grouting, the greater the loss of stratum, and the adverse effect on controlling stratum deformation. As shown in Table 3, the seepage rate of the synchronous grouting liquid for solidified slag is below 5.5%, and the stone rate is greater than 95%. Compared with the control group, the seepage rate is reduced and the stone rate is increased. This phenomenon is because the shield slag has a large specific surface area, which increases the water demand and thus reduces the water seepage rate. Since the fine particles in the shield slag contain clay and bentonite left over from construction, they have a certain water absorption capacity. Therefore, the shield slag has extremely high water retention and is not easy to consolidate and drain, making it difficult to reuse. However, this is of great benefit to reducing the water seepage rate of grouting materials and increasing the stone formation rate, avoiding the problem of traditional grouting materials being easy to seep and having a low stone formation rate. In addition, cement can increase the water retention of the grouting slurry. Increasing the amount of cement can increase the cohesion of the synchronous grouting slurry and prevent free water from seeping out from the slurry, thereby achieving the purpose of reducing the water seepage rate of the slurry.

[0094] Table 3 Water seepage rate and stone rate of synchronous grouting materials

[0095]

[0096] (4) Stone compressive strength

[0097] The slurry of synchronous grouting should have a certain strength after hardening, so that after the slurry fills the gap behind the wall, the slurry can connect the pipe segment and the surrounding soil into a whole, evenly bear the surrounding rock pressure outside the pipe segment, ensure the safety of the tunnel structure, and prevent surface settlement caused by stratum deformation. With the increase of curing age, the compressive strength of each slurry stone body tends to increase and the strength increases faster in the later period. Under the condition of a constant water-solid ratio, the slurry strength gradually increases with the increase of cement dosage. The hydration product produced by the cement hydration reaction is one of the strength providers of the synchronous grouting material for solidified soil. The more hydration products there are, the higher the slurry strength is. On the other hand, the compressive strength of the slurry increases with the decrease of the water-to-solid ratio. As the water content in the slurry system decreases, the distance between the slurry particles decreases, the connection between the solid particles becomes tighter, and the compressive strength of the slurry increases. Sand is the main filling aggregate in the slurry. An appropriate amount of sand can serve as a skeleton to improve the density and strength of the slurry, but an increase in the sand content will reduce the content of cement and slag, reduce the gel material produced by solidification, and reduce the compressive strength. The addition of shield slag enhances the compressive strength of the material. The shield slag particles are finer, and after it partially replaces the medium sand, the particle grading of the slurry system is denser and reasonable, filling the gaps between the medium sand and enhancing the compressive strength of the synchronous grouting material. On the other hand, the slag in the The clay minerals reacted with cement particles to form gelling materials to connect fine aggregates. The curing agent reacted with the slag particles, and the linear polymer compounds formed by the polymerization of epoxy resin monomers increased. The strength of the three-dimensional network structure formed by the linear polymer gradually increased. The slag particles were continuously filled in the grid structure of the three-dimensional network polymer. The filling and adsorption between the slag particles, sand particles, hydration products and polymers solidified the solidified soil slurry, thereby effectively improving the strength of the solidified slag slurry. The strength of the slurry increased after the treatment agent was added. When the dosage was 0.02%, the strength was greater than that of the control group. However, when the curing agent dosage increased from 0.02% to 0.04%, the compressive strength of the slurry decreased. This may be because the wrapping of the cement particles by the water-based epoxy film hindered the dissolution and hydration of the cement and prevented the formation of gelling materials.

[0098] (5) Optimal slurry ratio and performance

[0099] According to the above research results, taking into account the balance between fluidity and strength, the optimal ratio of shield slag synchronous grouting materials was determined, as shown in the table. The working performance and mechanical properties of the slurry with the optimal ratio were tested, and the results are shown in Table 5.

[0100] Table 4 Ratio of shield slag synchronous grouting materials

[0101]

[0102] Table 5 Performance of shield slag synchronous grouting materials

[0103]

[0104] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0105] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A shield slag synchronous grouting material, characterized in that: The grouting material is prepared from the following materials: 300-500 parts of cement, 100-200 parts of fine aggregate, 150-300 parts of fly ash, 500-1500 parts of bentonite, and 180-320 parts of curing agent.

2. The shield slag synchronous grouting material according to claim 1, characterized in that: The grouting material is prepared from the following materials: 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water.

3. The shield slag synchronous grouting material according to claim 1, characterized in that: The cement is ordinary Portland cement produced by Guangxi Guigang Cement Company, which has a fixed composition and stable performance. The strength grade is 42.5Pa. The fine aggregate is medium-fine sand screened from on-site slag.

4. The shield slag synchronous grouting material according to claim 1, characterized in that: The fly ash used is Class F Grade I fly ash, with a fineness of 9.2%, a water requirement ratio of 89%, a loss on ignition of 4.6%, a moisture content of 0.6%, and a SO3 of 1.

1.

5. The shield slag synchronous grouting material according to claim 1, characterized in that: Sodium bentonite is selected, and the chemical composition percentage of sodium bentonite is: SiO2 is 63.12%, Al2O3 is 15.23%, Fe2O 3为 5.50%, Na2O is 2.36%, MgO is 3.33, K2O is 1.98, and CaO is 1.

42.

6. The shield slag synchronous grouting material according to claim 1, characterized in that: The organic component of the photoinitiated latent slag solidifier is formed with water-based epoxy resin as the main agent and silicone waterproofing agent, photoinitiator and cellulose dispersant as external admixtures. The inorganic component is a composite of cement and various mineral components. The physical and mechanical indicators of the soil are changed through cementitious materials, turning the loose and weak slag into civil engineering materials with certain engineering properties.

7. A method for preparing shield slag synchronous grouting material, characterized in that: The preparation method comprises: S1: Prepare 320 parts of cement, 150 parts of fine aggregate, 320 parts of fly ash, 920 parts of bentonite, 240 parts of curing agent and 200 parts of water; S2: Use a stirrer to stir the materials at a low speed until they are evenly mixed; S3: Then the shield curing agent is mixed into water for dilution, and water is added to the material to reach the water-binder ratio required by the formula; S4: The agitator stirs at high speed until it is uniform, forming shield slag synchronous grouting liquid.

8. The method for preparing shield slag synchronous grouting material according to claim 7, characterized in that: The steps of S2 are: Prepare the required materials according to the formula ratio, including cement, fine aggregate, fly ash, bentonite, and curing agent; Set the mixer to a low speed to ensure that the materials are thoroughly mixed without excessive bubbles or separation. Put the pre-weighed cement, filler and other solid raw materials into the mixer in sequence; Start the agitator and continue to stir the materials at a low speed according to the designed stirring time; During the mixing process, stop the machine regularly to check the state of the mixture and adjust the speed of the agitator according to the state of the mixture; 9. The method for preparing shield slag synchronous grouting material according to claim 7, characterized in that: The steps of S3 are: Slowly add the shield curing agent into the prepared clean water; Use a stirrer to mix the curing agent and the aqueous solution; Calculate the required water-binder ratio based on the predetermined design formula; According to the calculated water-binder ratio, slowly add the previously diluted curing agent solution into the mixed shield slag synchronous grouting material. During the process of adding water, continue stirring to ensure that the curing agent solution and the material are evenly mixed. Mix the whole material with mixer at low speed.

10. The method for preparing shield slag synchronous grouting material according to claim 7, characterized in that: The steps of S4 are: Set the blender to high speed blending mode and start the blender; Continue stirring for 5-30 minutes in high-speed stirring mode; Stop the machine during the process to check the state of the mixture, check for lumps and stratification; After completing high-speed stirring, stop the machine to check the uniformity and fluidity of the mixture; After mixing is completed, the shield slag synchronous grouting liquid is immediately transported to the construction site.